Why does increasing public access to medicines differ between countries? Qualitative comparison of nine countries - Gauld, N.; Bryant, L.; Emmerton, Lynne; Kelly, F.; Kurosawa, N.; Buetow, S. (2015)
Objective: To identify factors associated with differences between developed countries in reclassifying (switching) medicines from prescription to non-prescription availability. Methods: Cross-national qualitative research using a heuristic approach in the US, UK, Japan, Australia and New Zealand, supplemented by data from Canada, Denmark, the Netherlands and Singapore. In-depth interviews with 80 key informants (65 interviews) explored and compared factors in terms of barriers and enablers to reclassification of medicines in each country. Document analysis supplemented interview data. Results: Each country had a unique mix of enablers and barriers to reclassification. Enablers included government policy (particularly in UK), pharmacist-only scheduling (particularly in Australia and New Zealand) and large market size (particularly in the US and Europe). Local barriers included limited market potential in small countries, the cost of a reclassification (particularly in the US), competition from distributors of generic medicines, committee inconsistency and consumer behavior. UK had more enablers than barriers, whereas in Australia the opposite was true. Conclusion: Different factors limit or enable reclassification, affecting consumer access to medicines in different countries. For countries attempting to reduce barriers to reclassification, solutions may include garnering government support for reclassification, support and flexibility from the medicines regulator, having a pharmacy-only and/or pharmacist-only category, providing market exclusivity, ensuring best practice in pharmacy, and minimizing the cost and delays of reclassification.